Implementasi Kebijakan Makan Bergizi Gratis dalam Perspektif Hak Asasi Manusia terhadap Pemenuhan Hak atas Pangan dan Gizi Masyarakat - Saifun Nufus; Sigit Kamseno; Wahyudi Wahyudi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Free Nutritious Meal Program (MBG) is a government policy to support the fulfillment of the public's right to food and nutrition. However, its implementation raises legal issues related to the state's constitutional obligations, budgeting and policy oversight. This study aims to analyze the implementation of the MBG from the perspective of human rights and the fulfillment of the community's social rights. The method used is normative legal research with a legislative and conceptual approach. The results show that the MBG has a strong constitutional basis in the 1945 Constitution as a manifestation of the state's responsibility to fulfill citizens' social rights. The novelty of this research lies in the analysis of the relationship between human rights, state authority, budgeting and oversight in the implementation of the MBG program.